PENGARUH DUKUNGAN ATASAN DAN PEMBERDAYAAN TERHADAP KINERJA PEGAWAI DIMODERASI IKLIM ORGANISASI (STUDI PADA KELURAHAN DIKABUPATEN SEMARANG) - Arif Kusumawardana, 1342020006 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The purpose of this study was to examine and analyze the influence of supervisor support and empowerment to employee performance of Villages throughout Semarang Regencymoderated organizational climate. This research is an explanatory research (explanatory research) with a qualitative approach. The research population is all employees of the Villages in Semarang Regency with the status of Civil Servants (PNS). The number of population of 131 people. Sampling was done using census techniques. The results showed that: (1) Support superiors positive and significant effect on employee performance. (2) Empowerment and significant positive effect on employee performance. (3) Organization climate moderate strengthen the support supervisor influence on employee performance. (4) Organization climate moderate strengthens empowerment influence on employee performance of Villages throughout Semarang Regency Keywords: supervisor support, empowerment, organizational climate and employee performance